Understanding Career Cushioning Underorganizational Instability: Job Crafting as a Moderator of the Relationship Between Perceived Organizational Instability and Employee Engagement - Supar Wasesa; Jaka Syahputra (Jurnal Sosial Sains dan Komunikasi, 2026)
The phenomenon of career cushioning, defined as employees' tendency to discreetly prepare alternative career opportunities without informing their current employer, has become increasingly prevalent in the wake of widespread layoffs and ongoing global economic uncertainty. This conceptual article aims to develop a theoretical framework that explains the relationships among perceived organizational instability, employee engagement, career cushioning, and job crafting. Unlike conventional employee engagement studies, which often conceptualize organizational loyalty as a relatively stable construct, this article argues that perceived organizational instability encourages employees to engage in career cushioning as a psychological self-protection mechanism, ultimately reducing their level of employee engagement. Furthermore, job crafting is proposed as a moderating variable that mitigates this negative relationship. Employees who proactively redefine their work tasks, interpersonal relationships, and the meaning of their work are expected to possess greater psychological resources, enabling them to remain engaged despite experiencing organizational uncertainty. This study employs a narrative literature review based on Job Insecurity Theory, Conservation of Resources Theory, the Job Demands–Resources Model, and Job Crafting Theory to develop a conceptual model consisting of five propositions for future empirical testing. The proposed framework contributes to the organizational behaviour and human resource management literature by extending the traditional concept of job insecurity to encompass more subtle and concealed defensive career behaviours. In addition, it offers practical implications for human resource practitioners in designing retention strategies and employee engagement initiatives that are better aligned with the challenges of an increasingly uncertain and dynamic work environment.